School Facilities Maintenance Strategies and Quality Education Delivery in Public Junior Secondary Schools, Lagos State - GBESOEVI, Emmanuel Semako; AKINYEMI, Isiaka Adeniran; OLUWATUNBI, Esther Adeola; Odumade Ashogbon, Akorede Serifat (Indonesian Journal of Economics, Social, and Humanities, 2024)
This study used five assumptions to guide the examination of the techniques for maintaining school infrastructure and providing high-quality education in public junior secondary schools in Lagos State Education District 1. All 42 public junior secondary school principals and teachers in the chosen education district made up the study's population, which used a descriptive and correlational research approach. 216 principals and teachers made up the sample, which was selected using multistage - stratified, simple random, and purposive selection approaches from the sampled 18 schools. A self-constructed questionnaire with two dimensions, one with 20 items on quality education delivery and the other dimension on school facilities maintenance strategies, were used to collect data for the study. For each dimension, the reliability coefficients for this instrument's were found to be 0.77 and 0.79, respectively with a face and content validity being ensured. Person product moment correlation analysis was used as an inferential statistical technique to analyze the data at the 0.05 level of significance. The research findings indicates a noteworthy correlation between preventative maintenance strategy(r = .813; N=216; p< .05), corrective maintenance strategy (r = .786; N=216; p< .05), routine maintenance strategy (r = .765; N=216; p< .05), emergency maintenance strategy (r = .745; N=216; p< .05), remedial maintenance strategy (r = .925; N=216; p< .05) and quality education delivery in Lagos State Education District I. The study thereafter concluded that school facilities maintenance strategies is apparently a major determining factor of quality education delivery in public junior secondary schools in Lagos State Education District I. Thus, the study's recommendations include, among other things, the requirement that maintenance practices and culture be ingrained in everyone and that all parties involved in the education sector bear responsibility for them in order to guarantee the delivery of high-quality education.